2022
DOI: 10.1002/cne.25437
|View full text |Cite
|
Sign up to set email alerts
|

The local and long‐range input landscape of inhibitory neurons in mouse auditory cortex

Abstract: Roughly 20% of the neurons in the mouse cortex are inhibitory interneurons (INs). Of these, the three major subtypes are parvalbumin (PV), somatostatin (SST), and vasoactive intestinal polypeptide (VIP) expressing neurons. We used monosynaptic rabies tracing to compare the presynaptic input landscape onto these three IN subtypes in the mouse primary auditory cortex (A1). We compared both local patterns of monosynaptic inputs as well as long‐range input patterns. The local monosynaptic input landscape to SST ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…Because most long-range intra-telencephalic projections are excitatory (Shepherd, 2013;Harris and Shepherd, 2015), odor enhancement may be due to excitation of ACx by direct Pir input, whereas odor suppression may arise from indirect input via local circuitry or via other brain regions. In our anterograde tracing experiments identifying Pir-recipient neurons, we observed that the TeA receives a large amount of Pir input (Fig 2 ), a finding that is consistent with previous studies (Tasaka et al, 2020(Tasaka et al, , 2023 and suggests that TeA is a region that might relay Pir input to ACx, ultimately affecting ACx activity. Together these results pave the way for future studies to disentangle the relative contributions of direct Pir input versus indirect pathways to auditory-olfactory integration in ACx, and how the Pir-to-ACx pathway interacts with other multimodal and higher-order brain circuity.…”
Section: Discussionsupporting
confidence: 91%
“…Because most long-range intra-telencephalic projections are excitatory (Shepherd, 2013;Harris and Shepherd, 2015), odor enhancement may be due to excitation of ACx by direct Pir input, whereas odor suppression may arise from indirect input via local circuitry or via other brain regions. In our anterograde tracing experiments identifying Pir-recipient neurons, we observed that the TeA receives a large amount of Pir input (Fig 2 ), a finding that is consistent with previous studies (Tasaka et al, 2020(Tasaka et al, , 2023 and suggests that TeA is a region that might relay Pir input to ACx, ultimately affecting ACx activity. Together these results pave the way for future studies to disentangle the relative contributions of direct Pir input versus indirect pathways to auditory-olfactory integration in ACx, and how the Pir-to-ACx pathway interacts with other multimodal and higher-order brain circuity.…”
Section: Discussionsupporting
confidence: 91%